A török hódoltság mint földrajzi régió - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2008)
The 150-year long Turkish occupation did not only hinder the development of Hungarian society regarding its social structure and its economy, it reshaped the spatial dimension of the Carpathian basin significantly as well. The emergence of the Great Plain as we know it today, the Puszta as a geographical factor came about thanks to the Turkish rule. The Turks occupied not only the Great Plain but significant territories of Transdanubia as well. So the Turkish Empire comprised of territories which were quite different and which did not form a homogeneous geographical region. The keeping of these territories together was a military issue, because one can notice the rare geographical phenomena that in this era military affairs meant the geographical region shaping power for a transitional period. Therefore the drawing of the geographical picture of the territories under Turkish rule can only happen by making use of the military geographical approach.